Students’ Self-Confidence and Their Willingness to Communicate in English - Invia Gorni Katiandagho; Virginia Gabrella Sengkey (Linguistic, English Education and Art (LEEA) Journal, 2022)
This study aimed to find out the level of students' self-confidence and the level of students' willingness to communicate in English. Furthermore, the main purpose of this study was to find out the correlation between students' self-confidence and their willingness to communicate in English. The researcher adapted the self-confidence questionnaire from Park and Lee (2004) cited in Ningsi (2020). Also, the willingness to communicate questionnaire from Horwitz, Horwitz, and Cope (1986) cited in Rihardini, Yaniafari, and Mukminatien, 2021). This study was conducted to grades 10, 11, and 12 of a private high school in North Sulawesi who were enrolled in the first semester of 2022/2023 academic year. The results were (1) students' self-confidence was moderate with a mean score 3.17; (2) students' willingness to communicate in English was moderate with a mean score 2.85; (3) there was a significant correlation between students' self-confidence and their willingness to communicate in English with r = 0 .575 and p =0.000 < α =0.05). Thus, teachers must try to motivate and find ways to help students be more confident so that the students will be more willing to communicate. Keywords: English, Self-confidence, Willingness to communicate